2021
DOI: 10.3390/plants10030481
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Chemical Adaptations of Artemisia monosperma Delile and Limbarda crithmoides (L.) Dumort. in Response to Arid Coastal Environments along the Mediterranean Coast of Egypt

Abstract: Arid coastal habitats are stressful regions subjected to the effects of biotic and abiotic factors. Vascular plants in these habitats display different responses to cope with these environmental fluctuations. This work addressed the morpho-anatomical features and chemical responses of two medicinal vascular plant species Artemisia monosperma Delile and Limbarda crithmoides (L.) Dumort., growing naturally along the Mediterranean coast of Egypt. Soil properties (physical and chemical), morpho-anatomical features… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 62 publications
2
6
0
Order By: Relevance
“…In the current study, the coastal soil supporting the studied halophytes was featured by its coarse sandy texture, alkaline range, low water holding capacity, low fertility (low organic matter, TN, TP, K + , Ca 2+, and Mg 2+ ), and high salinity. These findings were in agreement with reports that displayed that, the Mediterranean region hosts different types of soils with low amounts of organic matter, an acidic to alkaline range, and high salinity (Abdelaal et al, 2018;Ciccarelli, 2015;El-Sherbeny et al, 2021). Specifically, such low fertility and deficiency of organic matter along the coastal salt marshes habitat may be attributed to limited nutrient retention capacity and minerals bioavailability, degradation and erosive processes, scarce or irregular rainfall, and long, hot summers (Sardans and Peñuelas, 2013).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In the current study, the coastal soil supporting the studied halophytes was featured by its coarse sandy texture, alkaline range, low water holding capacity, low fertility (low organic matter, TN, TP, K + , Ca 2+, and Mg 2+ ), and high salinity. These findings were in agreement with reports that displayed that, the Mediterranean region hosts different types of soils with low amounts of organic matter, an acidic to alkaline range, and high salinity (Abdelaal et al, 2018;Ciccarelli, 2015;El-Sherbeny et al, 2021). Specifically, such low fertility and deficiency of organic matter along the coastal salt marshes habitat may be attributed to limited nutrient retention capacity and minerals bioavailability, degradation and erosive processes, scarce or irregular rainfall, and long, hot summers (Sardans and Peñuelas, 2013).…”
Section: Discussionsupporting
confidence: 92%
“…In addition, the total phenols and flavonoids reported for T. nilotica in this study were greater than the previous study estimating total phenols and flavonoids in T. nilotica . Previous literature reported that L. crithmoides contains significant levels of secondary metabolites such as phenolic acids, flavonoids, terpenoids, and essential oils (Adorisio et al, 2020;El-Sherbeny et al, 2021). Concerning soil physicochemical features associated with phytochemical components of the studied halophytes, lower concentrations of soil sulfates, total phosphorous and calcium induce a greater accumulation of total phenols and flavonoids in the studied halophytes.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…Limbarda crithmoïdes, well known as Golden samphire, is a succulent perennial coastal plant commonly found in the Mediterranean basin in salt water marsh areas (Zurayk and Baalbaki, 1996). It displays a fascinating capacity to tolerate high sodium concentrations in its aerial parts (Flowers and Colmer, 2008;Vicente and Boscaiu, 2020) allowing it to have salt, water, and metallic stress tolerance (Al Hassan et al, 2016;El-Sherbeny et al, 2021;Dridi et al, 2022a;2022b). L. crithmoïdes has long been collected for its medicinal properties and therapeutic uses.…”
Section: Introduction Introduction Introduction Introductionmentioning
confidence: 99%